Speciation of Uranyl Compound at Different pH and Its Precipitation Characteristics in Nitric Acid - michael santoso, samgar; gideon effendi, petrick; nugraha, tutun; listyorini, niken; adhi pratama, hendra (Liaison Journal of Engineering, 2023)
Uranyl is one of the most common chemical compounds that can be found in the waste of nuclear plants. As such, understanding the speciation of uranyl is important to ensure that the best waste treatment option is taken to purify the uranyl inside the waste, whether it is through flocculation, evaporation, or other waste treatment option. As most uranyl waste is either acidic or basic, different pH levels would be the basis of measurement for the speciation analysis of uranyl. Neutralizing the pH of the solution turns out to be the best method to separate uranyl compounds. Keywords: Speciation; pH; Uranyl; Solubility; Nitric Acid